2015
DOI: 10.1007/s00774-015-0692-0
|View full text |Cite
|
Sign up to set email alerts
|

Collagen production of osteoblasts revealed by ultra-high voltage electron microscopy

Abstract: In the bone, collagen fibrils form a lamellar structure called the "twisted plywood-like model." Because of this unique structure, bone can withstand various mechanical stresses. However, the formation of this structure has not been elucidated because of the difficulty of observing the collagen fibril production of the osteoblasts via currently available methods. This is because the formation occurs in the very limited space between the osteoblast layer and bone matrix. In this study, we used ultra-high-voltag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…They are essential in extra cellular matrix (ECM) which is the major component in tumor microenvironment and can regulate tumor cell behaviors [5,6]. Collagen proteins are produced and secreted by fibroblasts [7], osteoblasts [8], hematopoietic cells [9], and also can be biosynthesized and regulated by endothelial cells [10,11] and cancer cells [12]. Over the last few years, accumulated evidences have indicated that some collagens are differentially expressed in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…They are essential in extra cellular matrix (ECM) which is the major component in tumor microenvironment and can regulate tumor cell behaviors [5,6]. Collagen proteins are produced and secreted by fibroblasts [7], osteoblasts [8], hematopoietic cells [9], and also can be biosynthesized and regulated by endothelial cells [10,11] and cancer cells [12]. Over the last few years, accumulated evidences have indicated that some collagens are differentially expressed in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…One observation that also makes it unlikely that type 1 processes control predominant CFO is that the processes are perpendicular within the lamellae of alternating SOMs regardless of the lamella being dark or bright (27,69). We also suggest that pre-collagen molecules that are in a liquid crystalline phase (70) begin to orient within the osteoblast (41,71) in accordance with patterns of ciliary motion (▶ Fig. 9) prior to their evagination by fibropositors.…”
Section: Is One Period Of the Orthogonal Plywood Design A Truncated Pmentioning
confidence: 70%
“…To us it seems unlikely that this cell migration occurs during osteon formation because the osteoblasts are spatially constrained in circular/cylindrical groups when they form osteon lamellae. In a study of trabecular bone formation in embryonic chick calvaria, Hosaki-Takamiya et al (41) stated that "in order to form the lamellar structure, the [31]). (a and b) Two osteons with orthogonal plywood designs that have alternating fibril directions (but are not considered "alternating osteons") that give rise to either bright (a) or dark (b) type osteons, which are the result of their marked oblique-to-transverse orientation (bright, also see lower right image in ▶ Fig.…”
Section: Successive Osteoblast Synthesis Phases Make the Osteon Wallmentioning
confidence: 99%
“…In this study, we identified the initial steps of mineral formation in mouse calvaria, and found that osteoblasts first release collagen fibers, which is in accordance with previous studies showing the three dimensional morphometry of collagen fibrils during initial stages of mineralization. 14,15 Subsequently, osteoblasts secrete MVs in large amounts and can build a large bone area of 1200 μm in length in the initial 24 h.…”
Section: Discussionmentioning
confidence: 99%